Research and development in school : grounded in cultural historical activity theory - Postholm, May Britt (Brill/Sense, 2019)
"Research and Development in School: Grounded in Cultural Historical Activity Theory intends to give student teachers, teachers and school leaders research knowledge about which methodologies (research approaches) and methods (data collection and analysis methods) they can use as tools when researching the day-to-day affairs of school and classroom practice. Cultural historical activity theory (CHAT) is presented as the framework. When grounded in CHAT the intention of the research will be to produce useful knowledge whether the aim is to promote development when the research is conducted or incoming development processes. The text is useful in connection with CHAT-informed development work research (DWR), where development work and research are combined in a common project, and in connection with on-going practices in school without the person studying them supporting the on-going development work there and then, but with the intention and understanding that the constructed knowledge can be used in subsequent development processes. This book is also useful for teacher educators/researchers who supervise student teachers or collaborate with practitioners in schools. The wish is that CHAT and its models will be able to contribute to the development processes we want to see in school, which in turn will promote the pupils' learning outcome"--